Pendampingan Peningkatan Pendapatan UMKM Yang Terdampak Covid-19 Melalui Perbaikan Pengelolaan Manajemen Keuangan dan Pemasaran - Supardi; Yulianto, Mochamad Rizal; Sumarno (Procedia of Social Sciences and Humanities, 2022)
Mentoring aims to help increase the income of Micro, Small and Medium Enterprises affected by COVID-19 through improving financial management and marketing, especially for mousetrap producers. The development of the corona outbreak, it has an impact on several sectors, especially the economic and industrial sectors. Not a few companies that went out of business. Several companies have decided to lay off their employees and even terminate their employment. Including quantitative research using the results of a questionnaire survey filled out by respondents. The data analysis method used multiple linear regression analysis. To test the partial effect of the independent variables on the dependent variable, the t-test was used. The f test is used to test the effect of the independent variables together on the dependent variable. The results of data processing show that there is an effect of increasing the income of Micro, Small and Medium Enterprises affected by Covid-19 through improving financial management and marketing. together there is an effect of the independent variable on the dependent variable. Improving management and marketing management can increase the income of Micro, Small and Medium Enterprises affected by Covid-19.